2016
DOI: 10.1159/000449408
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Amyloid Beta and Tau Concentrations Are Not Modulated by 16 Weeks of Moderate- to High-Intensity Physical Exercise in Patients with Alzheimer Disease

Abstract: Background: Physical exercise may have some effect on cognition in patients with Alzheimer disease (AD). However, the underlying biochemical effects are unclear. Animal studies have shown that amyloid beta (Aβ), one of the pathological hallmarks of AD, can be altered with high levels of physical activity. Aim: The objective of this study was to elucidate the effect of 16 weeks of moderate- to high-intensity physical exercise on the biomarkers of AD, with special emphasis on the amyloidogenic pathway. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 43 publications
3
39
2
Order By: Relevance
“…This was observed for whole brain as well as for regional CBF in the frontal precuneus. The absence of detectable changes induced by the 16-week exercise intervention is in line with results from other modalities in this study ( Hoffmann et al, 2016 ; Sobol et al, 2016 ; Steen Jensen et al, 2016 ). Yet, an effect of exercise has been reported on several neuropsychological and physical function tests in the ADEX trial ( Hoffmann et al, 2016 ; Sobol et al, 2016 ).…”
Section: Discussionsupporting
confidence: 91%
“…This was observed for whole brain as well as for regional CBF in the frontal precuneus. The absence of detectable changes induced by the 16-week exercise intervention is in line with results from other modalities in this study ( Hoffmann et al, 2016 ; Sobol et al, 2016 ; Steen Jensen et al, 2016 ). Yet, an effect of exercise has been reported on several neuropsychological and physical function tests in the ADEX trial ( Hoffmann et al, 2016 ; Sobol et al, 2016 ).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, other studies showed no effects of exercise on Aβ levels in mouse models of AD 41,42 . Further, a patient study with exercise intervention found no effects on Aβ levels in CSF 43 , similar to what we observed in CSF from our 5xFAD mice. Hence, the clinical benefits regarding the effect of exercise on Aβ pathology in AD indicated in other experimental studies can be questioned.…”
Section: Discussionsupporting
confidence: 89%
“…However, we found no significant effect of EXE on our selected biomarkers. In a previous study, we also did not find effect on Ab species and tau/p-tau [9]. These markers, however, may provide novel insight into AD pathology and its progression [16,18,26].…”
Section: Discussioncontrasting
confidence: 44%
“…All subjects donated a blood sample before and after intervention and were tested at baseline and at 16 week follow-up with a comprehensive battery of tests of CF, activities of daily function, quality of life, physical activity, and neuropsychiatric symptoms. For details of inclusion and exclusion criteria, methods for inclusion, and cognitive and physical tests, see Steen Jensen et al [9]. A subgroup of 56 subjects recruited from three of eight centers had a lumbar puncture performed to collect CSF samples before and after intervention.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation